Editor's Choice: Deliberative and non-deliberative effects of descriptive and injunctive norms on cancer screening behaviors among African Americans. Issue 7 (2nd July 2020) - Manning, Mark; Lucas, Todd; Davis, Stacy N.; Valdimarsdottir, Heiddis B.; Thompson, Hayley
Abstract: Objective: Two longitudinal studies examined whether effects of subjective norms on secondary cancer prevention behaviors were stronger and more likely to non-deliberative (i.e., partially independent of behavioral intentions) for African Americans (AAs) compared to European Americans (EAs), and whether the effects were moderated by racial identity. Design: Study 1 examined between-race differences in predictors of physician communication following receipt of notifications about breast density. Study 2 examined predictors of prostate cancer screening among AA men who had not been previously screened.Main Outcome Measures: Participants' injunctive and descriptive normative perceptions; racial identity (Study 2); self-reported physician communication (Study 1) and PSA testing (Study 2) behaviors at follow up. Results: In Study 1, subjective norms were significantly associated with behaviors for AAs, but not for EAs. Moreover, there were significant non-deliberative effects of norms for AAs. In Study 2, there was further evidence of non-deliberative effects of subjective norms for AAs. Non-deliberative effects of descriptive norms were stronger for AAs who more strongly identified with their racial group. Conclusion: Subjective norms, effects of which are non-deliberative and heightened by racial identity, may be a uniquely robust predictor of secondary cancer prevention behaviors for AAs. Implications for targeted screening interventions are discussed.